Plan de mejoramiento para la empresa "La Crepería Express” ubicada en la ciudad de Armenia (2014)
The following work consists to develop an improvement plan to LA CREPERIA EXPRESS restaurant which is located in Armenia city, taking into account some aspects such us: Marketing, technical, administrative, legal, social, environmental and financial. At LA CREPERIA EXPRESS you will find Arabic food, crepes, salads and confectionery. This improvement plan was created from the need that the company applies the administrative tools for its benefits in all fields analyzing them to create strategies and recommendations for bringing this company to continue being increasingly successful. Moreover, to achieve the analysis in every single field we used MMGO which was developed in the improvement plan. Also, with the analysis help the improvement plan is presented in medium and long term to implement the results of this project and finally find daily good results that benefit the progress and the restaurant expansion as the current owner wants to achieve